A Comparison of the Stochastic Processes of Structural and Time-Series Exchange-Rate Models - Ahking, Francis W.; Miller, Stephen M. (The Review of Economics and Statistics, 1987)
Arnold Zellner and Franz Palm (1974) show that comparing the actual with the implied stochastic process es generating the endogenous variables in a system of dynamic structu ral equations provides important information about the system's corre ct specification. The authors apply their methodology to structural e xchange-rate models. They find that the log of the bilateral exchange rate is generally well approximated by a random-walk model. Thus, th e stochastic processes generating the exogenous variables should also be random-walk models, which in not borne out by our empirical resul ts. They suggest a reconciliation of their results based on a decompo sition technique developed by Stephen Beveridge and Charles R. Nelson (1981). Copyright 1987 by MIT Press.